1962
DOI: 10.1002/app.1962.070062314
|View full text |Cite
|
Sign up to set email alerts
|

Stress crazing of some amorphous thermoplastics

Abstract: Tensile stress‐induced crazing in polystyrene, poly(methyl methacrylate), and polycarbonate has been carefully examined by optical and electron microscopy. Examination of the surface of crazed specimens and the cross sections of individual crazes leads to the conclusion that the crazes are not void cracks, but are filled with a craze matter. The craze matter is readily distinguishable from the surrounding resin and is seen to exist in continuity with it. Further experiments confirm the existence of the craze m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

1967
1967
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(24 citation statements)
references
References 9 publications
1
22
0
1
Order By: Relevance
“…al, 1992). This interpretation is also supported by the observation that the craze disappears above glass transition temperature due to contraction of oriented fibrils (Spurr and Niegisch, 1962;Freidin, 1989). Standing on this view point, the voids inside craze are secondly generated by lateral constraint of normal Poisson contraction following the fibril elongation, as noted by Brady and Yeh (1973).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…al, 1992). This interpretation is also supported by the observation that the craze disappears above glass transition temperature due to contraction of oriented fibrils (Spurr and Niegisch, 1962;Freidin, 1989). Standing on this view point, the voids inside craze are secondly generated by lateral constraint of normal Poisson contraction following the fibril elongation, as noted by Brady and Yeh (1973).…”
Section: Introductionmentioning
confidence: 66%
“…The crazing is a phenomenon followed by initiation and growth of many crazes. Each craze is well known as a crackshaped micro-deformed region, in which a number of fibrils aligned in tensile principal stress direction are spaced in a row, as early observed by Spurr and Niegisch (1962). The study of Yang et al (1993) for a craze in PS by scanning force microscopy (SFM) has revealed the formation of craze with such a fibrillated structure to be a micro-necking process.…”
Section: Introductionmentioning
confidence: 97%
“…Striations transverse to the extension axis have been observed in a large number of polymers [ 1,2,4,9,[13][14][15]. Sometimes, as in a report by Spurr and Niegisch [ 15 ] , the discussion is in terms of crazing, but the events taking place seem to have parallels with those in wool fibers under extension.…”
Section: Introductionmentioning
confidence: 84%
“…According to this mechanism, surface microcracks are produced by environmentally-induced stresses in conjunction with resin degradation. The stresses are caused by differential dimensional changes (strains) induced by humidity and temperature ( [2], [3], [20]) as a result of the inherent micro-and macroheterogeneity of plastic-based materials ( [21]- [23]). Since these stresses are mainly due to cyclic fluctuations, they exert a type of stress-fatigue on the material.…”
Section: Surface Crackingmentioning
confidence: 99%